PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATERI INDONESIAKU KAYA BUDAYA BERBASIS KEARIFAN LOKAL DI KABUPATEN KEDIRI BAGI SISWA KELAS IV SDN SUMBEREJO 1 - Permatasari, Meilina; Ilmawati Fahmi Imron; Karimatus Saidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the fact that conventional classroom learning often makes students feel bored and unable to understand the material presented. This causes learning to be ineffective and the interaction between teachers and students to be passive. Many students have difficulty understanding the material, as seen in the results of the final assessment on the material "My Indonesia is Rich in Culture". As many as 80% of students cannot accept conventional teacher learning, and only 9-15% of students can understand the material well. Therefore, changes are needed in learning methods to improve the effectiveness and learning outcomes of students. Based on this background, several problem formulations emerged, namely: (1) How is the validity of I-spring-based interactive multimedia on the material "My Indonesia is Rich in Culture Based on Local Wisdom of Kediri Regency" at SDN Sumberejo 1? (2) How is the practicality of using I-spring-based interactive multimedia on the material "My Indonesia is Rich in Culture Based on Local Wisdom of Kediri Regency" for students as an independent learning medium at SDN Sumberejo 1? (3) How effective is I-spring based interactive multimedia on the material "My Indonesia is Rich in Culture Based on Local Wisdom of Kediri Regency" for students at SDN Sumberejo 1? The purpose of this study was to determine the validity, practicality, and effectiveness of the use of interactive multimedia learning media to be applied to elementary school students at SDN Sumberejo 1. This study used the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through questionnaires, interviews, and evaluation questions, with data analysis based on the criteria of validity, effectiveness, and practicality. The results of the study showed that this interactive multimedia was valid with an average of 84% in the media validity test and 84% in the material validity test, in the practicality test it was said to be very practical with an average percentage of 91% in the limited trial and an average percentage of 85% in the broad trial, and very effective with an average of 100% in the limited trial and 100% in the broad trial. The conclusion of this study is that interactive multimedia based on "Local Wisdom of Kediri Regency" for 4th grade elementary school students is effective for use during the learning process.